Method for modifying Prussian blue sodium battery positive electrode material by solvothermal method and positive electrode material prepared by method
The solvothermal method is used to form an iron element coating on the surface of Prussian blue sodium electropositive electrode material, which solves the problem of low water absorption and conductivity of the material, significantly improves the electrochemical performance and stability of the material, and achieves a higher Rate performance and cycle performance.
Patent Information
- Application Number
- CN202411073780.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Prussian blue sodium electropositive electrode materials have poor cycle stability, low Coulomb efficiency and obvious potential polarization due to lattice vacancy, crystal water, low electron conductivity and side reactions between the electrode and the electrolyte. Current modification methods such as oxidation The material coating has low conductivity and is difficult to achieve effective modification under high temperature conditions.
Fe(CO)5 is reacted with Prussian blue sodium electropositive electrode material under a protective atmosphere to form an iron element coating layer. The iron element coating modified Prussian blue sodium is prepared by ultrasonic dispersion and solvothermal reaction. Electrode material reduces water absorption and improves conductivity and interface stability.
It effectively reduces the water absorption of the material, improves the conductivity and interface stability, enhances the rate performance and cyclic performance of the material, inhibits electrochemical interface side reactions, and significantly improves the electrochemical kinetics and stability of the material.
Smart Images

Figure CN119118155A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries, and particularly relates to a method for modifying a Prussian blue sodium-ion positive electrode material by a solvent thermal method and a positive electrode material prepared by the method. Background Art
[0002] Prussian blue-based sodium cathode materials are composed of a three-dimensional framework structure, which can provide a wide channel for the insertion and extraction of sodium ions, and are an ideal cathode material for sodium ion batteries. Although Prussian blue-based sodium cathode materials have the characteristics of open framework structure, excellent chemical stability, adjustable redox potential and excellent electrochemical activity, due to lattice vacancies, crystal water, poor electronic conductivity and side reactions between electrodes and electrolytes in the crystal structure, Prussian blue-based sodium cathode materials often have shortcomings such as poor cycle stability, low Coulomb efficiency and obvious potential polarization. Therefore, how to improve the structural and interfacial stability of Prussian blue-based sodium cathode materials has become a key issue that needs to be urgently solved in academia and industry.
[0003] In order to solve the structural stability problems caused by lattice vacancies and crystal water, the quality of crystals is improved by adjusting the preparation method, or the crystal element composition is further adjusted by element doping to optimize the crystal bulk structure. In addition, element doping can also improve the electronic conductivity and Na + The effect of the migration rate. In addition to the important influence of the intrinsic structure of the crystal on the electrochemical performance of sodium-ion batteries, the interfacial side reaction problem between the material and the electrolyte will inevitably deteriorate the performance of Prussian blue-based sodium cathode materials. After obtaining relatively high-quality Prussian blue-based sodium cathode materials by adjusting the preparation method and element doping, how to further improve the electrochemical performance of the material from the perspective of the interface is also one of the important future research directions of academia and industry. The main method is to modify the crystal surface by coating.
[0004] CN113921798A, CN115411260A and CN114620758A disclose the technical means of coating a layer of oxide on the surface of Prussian blue sodium positive electrode materials. After the surface coating modification of the oxide, the material is prevented from directly contacting with the electrolyte and air, the interface stability is improved, and the water absorption can be suppressed, and the cycle performance of the material is improved. However, the conductivity of the coated oxide is extremely low, and the coating on the surface of the material is not conducive to the transmission of electrons during the high-rate charge and discharge process.
[0005] Therefore, it is becoming increasingly important to find a coating material with a stable structure and high conductivity to simultaneously solve the problems of poor electrochemical kinetics and stability caused by the inherent low conductivity of Prussian blue sodium cathode materials and the interfacial side reactions with the electrolyte. Metal elements with excellent electronic conductivity and high tap density are a relatively ideal coating material. However, in order to achieve the technical effect of metal element coating modified cathode materials, a high-temperature heat treatment process is generally required, and the required temperature conditions are generally greater than 500°C, which is much higher than the decomposition temperature of 350°C of Prussian blue materials. Therefore, the use of this type of coating modification scheme faces huge technical difficulties. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a Prussian blue sodium-based positive electrode material modified by a solvothermal method, so as to achieve the beneficial effect of reducing the water absorption of the Prussian blue sodium-based positive electrode material, and at the same time achieve the purpose of improving the material conductivity and interface stability; the purpose of the present invention is also to provide an iron element-coated modified Prussian blue sodium-based positive electrode material prepared by the above method.
[0007] In order to solve the above technical problems, the preparation method of the present invention comprises the following steps: (1) mixing an organic solvent and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 2 to 8 hours to prepare a suspension A having a solid content of 5 to 75 wt %; (2) adding an appropriate amount of Fe(CO)5 to the suspension A obtained in step (1) under protective atmosphere conditions, controlling the mass ratio of Fe element to Prussian blue sodium cathode material to be 0.005-0.05:1, and stirring for 0.5-4h to obtain suspension B; (3) Transferring the suspension B to a reactor under protective atmosphere and performing a solvothermal reaction to obtain a precipitate; (4) Washing the precipitate obtained in step (3) with deionized water and ethanol, and vacuum drying the washed precipitate to obtain a Prussian blue sodium-based positive electrode material coated with iron.
[0008] In the step (1), the organic solvent includes one of diethyl ether, acetone, benzene and ethanol; preferably, the organic solvent includes one of diethyl ether and benzene; more preferably, the organic solvent is benzene.
[0009] In the step (1), the Prussian blue sodium positive electrode material includes one of an iron-based Prussian blue sodium positive electrode material, an iron-manganese-based Prussian blue sodium positive electrode material, an iron-cobalt-based Prussian blue sodium positive electrode material, an iron-nickel-based Prussian blue sodium positive electrode material, and an iron-copper-based Prussian blue sodium positive electrode material.
[0010] In the step (1), the ultrasonic dispersion time is 3 to 7 hours; preferably, the ultrasonic dispersion time is 4 to 6 hours.
[0011] In the step (1), the solid content of the suspension A is 15-65wt%; preferably, the solid content of the suspension A is 30-40wt%.
[0012] In the step (2), the mass ratio of Fe element to Prussian blue sodium positive electrode material is 0.015-0.04:1; preferably, the mass ratio of Fe element to Prussian blue sodium positive electrode material is 0.025-0.035:1.
[0013] In the step (2), the protective gas includes one of argon, nitrogen and helium; preferably, the protective gas includes one of argon and nitrogen; more preferably, the protective gas is nitrogen.
[0014] In the step (2), the stirring speed is 50 to 850 r / min; preferably, the stirring speed is 150 to 750 r / min; more preferably, the stirring speed is 400 to 500 r / min.
[0015] In the step (2), the stirring time is 1 to 3.5 hours; preferably, the stirring time is 2 to 2.5 hours.
[0016] In the step (3), the protective gas includes one of argon, nitrogen and helium; preferably, the protective gas includes one of argon and nitrogen; more preferably, the protective gas is nitrogen.
[0017] In the step (3), the solvent thermal reaction temperature is 150-260°C; preferably, the solvent thermal reaction temperature is 170-240°C; more preferably, the solvent thermal reaction temperature is 200-220°C.
[0018] In the step (3), the solvent thermal reaction time is 4 to 20 hours; preferably, the solvent thermal reaction time is 7 to 17 hours; more preferably, the solvent thermal reaction time is 11 to 13 hours.
[0019] In the step (4), the vacuum drying temperature is 120-230°C; preferably, the vacuum drying temperature is 140-210°C; more preferably, the vacuum drying temperature is 170-190°C.
[0020] In the step (4), the vacuum drying time is 10 to 26 hours; preferably, the vacuum drying time is 14 to 22 hours; more preferably, the vacuum drying time is 17 to 19 hours.
[0021] The present invention also provides a Prussian blue sodium-based positive electrode material modified by iron element coating, wherein the Prussian blue sodium-based positive electrode material modified by iron element coating is prepared by the above method; the positive electrode material comprises a Prussian blue sodium-based positive electrode material matrix and an iron element coating layer.
[0022] The method provided by the present invention and the obtained Prussian blue sodium-based positive electrode material coated with iron element have the following beneficial effects: (1) Iron is insoluble in water and does not react easily with water. The present technical solution can avoid direct contact between the base material and water by coating a layer of iron on the surface of the Prussian blue sodium cathode material, thereby reducing its water absorption and improving the processing performance of the Prussian blue sodium cathode material.
[0023] (2) The presence of iron prevents direct contact between the electrolyte and the matrix material, thereby reducing the corrosion of the Prussian blue sodium cathode material matrix by HF formed by trace water in the electrolyte, thereby achieving the beneficial effect of improving the material's cycle performance.
[0024] (3) HF formed by trace water in the electrolyte reacts with the iron coating to form FeF2, a phase-change cathode material. FeF2 plays a role in passivation protection, inhibiting the occurrence of electrochemical interface side reactions and increasing the electrochemical interface stability of the material.
[0025] (4) Elemental iron has extremely high electrical conductivity. Coating it on the surface of the matrix material can solve the problems of poor electrochemical kinetics and stability caused by the inherent low electrical conductivity of Prussian blue-based sodium cathode materials, thereby improving the rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The charge and discharge curves at 0.1C of the iron-based Prussian blue sodium-based cathode material modified by iron element coating prepared in Example 1 of the present invention and the iron-based Prussian blue sodium-based cathode material of the comparative example.
[0027] Figure 2 This is an X-ray diffraction (XRD) pattern of the iron-based Prussian blue sodium-based cathode material modified by iron element coating prepared in Example 1 of the present invention.
[0028] Figure 3 This is a scanning electron microscope (SEM) image of the iron-based Prussian blue sodium-based cathode material modified by iron element coating prepared in Example 1. (Abstract attached) Figure 4 This is a scanning electron microscope (SEM) image of the iron-manganese-based Prussian blue sodium-like positive electrode material in the comparative example of the present invention without any treatment.
[0029] Figure 5 This is an electron image collected when performing energy dispersive X-ray spectroscopy analysis on the iron-based Prussian blue-like sodium-based cathode material coated with iron element modified in Example 1 of the present invention.
[0030] Figure 6 for Figure 5 Energy dispersive X-ray spectroscopy (EDS) of selected areas. DETAILED DESCRIPTION
[0031] In order to make the present invention more obvious and easy to understand, the technical solution of the present invention is further explained below through embodiments in combination with the drawings, but it is not intended to limit the protection scope of the present invention.
[0032] In the present invention, the Prussian blue sodium positive electrode material includes but is not limited to one of an iron-based Prussian blue material, an iron-manganese-based Prussian blue material, an iron-cobalt-based Prussian blue material, an iron-nickel-based Prussian blue material, and an iron-copper-based Prussian blue material. The Prussian blue sodium positive electrode material selected in the embodiment of the present invention is an iron-manganese-based Prussian blue material. Example 1
[0033] Benzene and iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 5 hours to obtain a suspension A with a solid content of 35wt%; the mass ratio of Fe element to iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.030:1, and an appropriate amount of Fe(CO)5 was added to suspension A under nitrogen protection, and stirred at 450r / min for 2.25 hours to obtain suspension B; suspension B was transferred to a reactor under nitrogen protection, and a solvent thermal reaction was carried out at 210℃ for 12 hours to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 180℃ for 18 hours to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element.
[0034] Fe(CO)5 is easily decomposed to form iron and carbon monoxide when heated. Using the solvent thermal reaction modification process, the iron formed by the thermal decomposition of Fe(CO)5 will deposit the iron-manganese-based Prussian blue sodium-type cathode material to form a surface coating layer. The iron coated on the surface of the iron-manganese-based Prussian blue sodium-type cathode material is insoluble in water and not easy to react with water. The iron coating layer can avoid direct contact between the base material and water, reduce its water absorption, and improve the processing performance of the Prussian blue sodium-type cathode material. The presence of iron can avoid direct contact between the base material and the electrolyte, thereby inhibiting the occurrence of electrochemical interface side reactions, increasing the interface stability of the material, and achieving the beneficial effect of improving the material's cycle performance. Iron has extremely high electrical conductivity. Coating on the surface of the base material can solve the problems of poor electrochemical kinetics and stability caused by the inherent low electrical conductivity of the Prussian blue sodium-type cathode material, thereby improving the material's rate performance.
[0035] Figure 1The first charge and discharge curves of the materials obtained in Example 1 and the comparative example at 0.1C are shown. It can be seen from the figure that the 0.1C discharge capacity of the material in Example 1 is about 5 mAh / g higher than that in Comparative Example 1. In addition, the coulombic efficiency of the first charge and discharge of the material obtained in Example 1 is 97.0%, while the first efficiency of the material in Comparative Example 1 is only 90.2%. This can explain that after the iron element is coated and modified, the problem of poor electrochemical kinetics and stability caused by the interface side reaction between the substrate and the electrolyte is solved, the interface stability of the material is increased, and the side reaction between the electrolyte and the interface is suppressed during the charge and discharge process.
[0036] Figure 2 The X-ray diffraction (XRD) diagram of the iron-based Prussian blue sodium-type positive electrode material prepared in Example 1 of the present invention, which shows that after the iron-based Prussian blue sodium-type positive electrode material is modified by the solvothermal process, the structure of the iron-based Prussian blue sodium-type positive electrode material does not change, and the main characteristic peaks in the X-ray diffraction (XRD) diagram are consistent with the iron-based Prussian blue sodium-type positive electrode material, indicating that the iron-based Prussian blue sodium-type positive electrode material is not destroyed by the solvothermal process. A weak characteristic peak of iron appears at 44.5°, which indicates that this technical solution successfully forms an iron-based coating layer on the surface of the Prussian blue sodium-type positive electrode material. Example 2
[0037] Ether and iron-manganese-based Prussian blue sodium-type cathode material were mixed and ultrasonically dispersed for 6 hours to obtain a suspension A with a solid content of 40wt%; the mass ratio of Fe element to iron-manganese-based Prussian blue sodium-type cathode material was controlled to be 0.025:1, and an appropriate amount of Fe(CO)5 was added to suspension A under argon protection, and stirred at 500r / min for 2.5 hours to obtain suspension B; suspension B was transferred to a reactor under argon protection, and a solvent thermal reaction was carried out at 220℃ for 11 hours to obtain a precipitate; the precipitate obtained in the step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 190℃ for 17 hours to obtain an iron-based Prussian blue sodium-type cathode material coated with iron element. Example 3
[0038] Acetone and an iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 4 hours to obtain a suspension A with a solid content of 30wt%; the mass ratio of Fe element to the iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.035:1, and an appropriate amount of Fe(CO)5 was added to the suspension A under the protection of helium, and stirred at 400r / min for 2 hours to obtain a suspension B; the suspension B was transferred to a reactor under the protection of helium, and a solvent thermal reaction was carried out at 200℃ for 13 hours to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 170℃ for 19 hours to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element. Example 4
[0039] The ethanol and the iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 7 hours to obtain a suspension A with a solid content of 65wt%; the mass ratio of the Fe element to the iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.04:1, and an appropriate amount of Fe(CO)5 was added to the suspension A under nitrogen protection, and stirred at 750r / min for 3.5 hours to obtain a suspension B; the suspension B was transferred to a reactor under nitrogen protection, and a solvent thermal reaction was carried out at 240℃ for 7 hours to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 140℃ for 22 hours to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element. Example 5
[0040] Benzene and iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 3 hours to obtain a suspension A with a solid content of 15wt%; the mass ratio of Fe element to iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.015:1, and an appropriate amount of Fe(CO)5 was added to suspension A under nitrogen protection, and stirred at 150r / min for 1 hour to obtain suspension B; suspension B was transferred to a reactor under nitrogen protection, and a solvent thermal reaction was carried out at 170℃ for 17 hours to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 210℃ for 14 hours to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element. Example 6
[0041] Benzene and iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 8 hours to obtain a suspension A with a solid content of 75wt%; the mass ratio of Fe element to iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.005:1, and an appropriate amount of Fe(CO)5 was added to suspension A under nitrogen protection, and stirred at 850r / min for 4 hours to obtain suspension B; suspension B was transferred to a reactor under nitrogen protection, and a solvent thermal reaction was carried out at 260℃ for 4 hours to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 120℃ for 26 hours to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element. Example 7
[0042] Benzene and iron-manganese-based Prussian blue sodium-type positive electrode material were mixed and ultrasonically dispersed for 2 hours to obtain a suspension A with a solid content of 5wt%; the mass ratio of Fe element to iron-manganese-based Prussian blue sodium-type positive electrode material was controlled to be 0.05:1, and an appropriate amount of Fe(CO)5 was added to suspension A under nitrogen protection, and stirred at 50r / min for 0.5h to obtain suspension B; suspension B was transferred to a reactor under nitrogen protection, and a solvent thermal reaction was carried out at 150℃ for 20h to obtain a precipitate; the precipitate obtained in the washing step was washed with deionized water and ethanol. The washed precipitate was vacuum dried at 230℃ for 10h to obtain an iron-based Prussian blue sodium-type positive electrode material coated with iron element.
[0043] In order to illustrate the necessity of each technical link of the present invention for the beneficial effects, the following comparative examples are implemented. Comparative Example
[0044] An iron-manganese-based Prussian blue sodium-based positive electrode material without any treatment was used as a comparative example.
[0045] The material prepared by the process of the embodiment and the comparative example is immediately used as an active material to prepare a positive electrode sheet for the assembly test of a sodium ion battery.
[0046] The preparation process of the positive electrode is as follows: the positive electrode is composed of four parts: active material, conductive agent, binder and current collector. Acetylene black is used as the conductive agent, 10mg / ml polyvinylidene fluoride (PVDF) N-methylpyrrolidone (NMP) solution is used as the binder, the active material, conductive agent and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1 and ground into a slurry with suitable viscosity, and then the slurry is evenly coated on the aluminum foil. The coated electrode is placed in a vacuum drying oven at 100°C and dried for 16 hours. After drying, it is punched into a small disc with a diameter of 10mm by a punching machine, and finally the battery is assembled in a glove box in an argon atmosphere.
[0047] The battery assembly process is as follows: the prepared positive electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, 300μL of 1mol / L sodium perchlorate electrolyte is added, the electrolyte solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1, and 5% fluoroethylene carbonate (FEC) is added to the electrolyte as an additive. The button half-cell is assembled in the order of the negative electrode shell, sodium sheet, diaphragm, positive electrode, gasket, shrapnel, and positive electrode shell, and finally packaged in a glove box using a button battery sealing machine.
[0048] The assembled button half-cell adopts constant current charge and discharge mode in the voltage range of 2.0 to 4.0 V to carry out corresponding electrochemical performance tests.
[0049] In addition, in order to test the storage performance of the material, the materials prepared by the process of Example 1 and the comparative example were exposed to air for 20 hours to prepare electrode sheets and assembled batteries for corresponding electrochemical performance tests. The samples were marked as Example 1-20h and Comparative Example-20h, respectively.
[0050] The electrochemical performance test results of each material are shown in Table 1.
[0051]
[0052] The embodiments are all better than the comparative examples, which shows that the electrochemical properties of the material can be significantly improved after the surface coating of the iron element. Among all the embodiments, Example 1 has the best electrochemical performance. By comparing the discharge specific capacity of Example 1 with that of the comparative example, it can be seen that the difference in discharge specific capacity at 0.1C is relatively small, only 5mAh / g. However, as the discharge rate gradually increases, the difference in discharge specific capacity between the two becomes larger and larger. At 10C and 20C, the discharge specific capacity of Example 1 is 27.2mAh / g and 30.9mAh / g higher than that of the comparative example, respectively. This shows that the conductivity of the material is greatly improved after the iron element coating modification using this process scheme, which solves the problem of poor electrochemical kinetics and stability caused by the inherent low conductivity of Prussian blue sodium cathode materials, thereby greatly improving the rate performance of the material. In Example 1 and the samples after being set aside for 20 hours, the difference in discharge capacity at different rates from 0.1C to 20C is extremely small, not exceeding 1 mAh / g, and the difference in capacity retention rate after 1200 cycles at 5C does not exceed 1%; the difference in discharge capacity at different rates of the samples of the comparative example set aside for 20 hours is relatively large, with a capacity difference of up to 19.9 mAh / g at 10C discharge, a capacity difference of up to 27.1 mAh / g at 20C discharge, and a capacity retention rate difference of 11.3% at 5C cycles for 1200 weeks. This indicates that the use of the present technical solution to coat the Prussian blue sodium-based cathode material with iron can modify and inhibit the water absorption of the material when exposed to the air, improve the storage stability of the material, and help to improve the processing performance of the material.
[0053] The 5C cycle 1200-week capacity retention rate of each embodiment is not less than 82%, and the 20C high-discharge capacity is greater than 117 mAh / g, which is better than the comparative example. From these two points of comparison, it can be seen that the iron single substance coating layer formed on the surface of the material by the technical solution of the present invention can solve the problem of poor electrochemical kinetics and stability caused by the interface side reaction between the Prussian blue sodium cathode material and the electrolyte, thereby improving the rate performance and cycle performance of the material.
[0054] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for modifying a Prussian blue sodium cathode material by a solvothermal method, characterized in that: The following steps are involved: (1) mixing an organic solvent and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 2 to 8 hours to prepare a suspension A having a solid content of 5 to 75 wt %; (2) adding an appropriate amount of Fe(CO)5 to the suspension A obtained in step (1) under protective atmosphere conditions, controlling the mass ratio of Fe element to Prussian blue sodium cathode material to be 0.005-0.05:1, and stirring for 0.5-4h to obtain suspension B; (3) Transferring the suspension B to a reactor under protective atmosphere and performing a solvothermal reaction to obtain a precipitate; (4) Washing the precipitate obtained in step (3) with deionized water and ethanol, and vacuum drying the washed precipitate to obtain a Prussian blue sodium-based positive electrode material coated with iron.
2. The method for modifying Prussian blue sodium cathode material by solvothermal method according to claim 1, characterized in that: In the step (1), the organic solvent includes one of ether, acetone, benzene and ethanol; the Prussian blue sodium positive electrode material includes one of iron-based Prussian blue sodium positive electrode material, iron-manganese-based Prussian blue sodium positive electrode material, iron-cobalt-based Prussian blue sodium positive electrode material, iron-nickel-based Prussian blue sodium positive electrode material and iron-copper-based Prussian blue sodium positive electrode material.
3. The method for modifying Prussian blue sodium cathode material by solvothermal method according to claim 1, characterized in that: In the step (2), the protective gas includes one of argon, nitrogen and helium; and the stirring speed is 50 to 850 r / min.
4. The method for modifying Prussian blue sodium positive electrode materials by solvothermal method according to claim 1, characterized in that: In the step (3), the protective gas includes one of argon, nitrogen and helium; the solvent thermal reaction temperature is 150 to 260° C., and the solvent thermal reaction time is 4 to 20 hours.
5. The method for modifying Prussian blue sodium cathode material by solvothermal method according to claim 1, characterized in that: In the step (4), the vacuum drying temperature is 120 to 230° C., and the vacuum drying time is 10 to 26 hours.
6. A Prussian blue sodium cathode material modified by a solvothermal method, characterized in that: The Prussian blue sodium positive electrode material coated with iron element and modified is prepared by the method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Method for rapidly preparing Prussian blue or analogues thereof in batches and application of Prussian blue or analogues thereof
CN113104862A
Preparation method of modified Prussian blue sodium battery positive electrode material and positive electrode material prepared by method
CN115377402A
Method for preparing sodium ferric phosphate by taking pentacarbonyl iron as iron source
CN116332143A
Method for vapor deposition of carbon-coated modified Prussian blue sodium battery positive electrode material and positive electrode material prepared by method
CN117165914A
Preparation method for low-defect prussian blue-type positive electrode material and use thereof
WO2024066192A1
